ART and the Placenta: An Invited Opinion - Gendie E. Lash (Fertility & Reproduction, 2025)
It is now well known that there is an increased risk of obstetric complications in pregnancies conceived by assisted reproductive technologies (ART). But is it all the fault of the placenta? And if so, is there anything we can do about it? Current evidence from both human and animal studies does suggest that there are placentation defects in ART pregnancies, though how these defects are manifested is currently unclear. As to whether anything can be done about it, I think the simple answer at this stage is no. However, an understanding of the different complications that may arise in an ART pregnancy will allow for better screening, monitoring, and early intervention when required in the absence of any curative solutions.